Mutation Identification in Sugarcane Somaclones Using Simple Sequence Repeat Markers (SSR) - Kerdkhong, Chommanat; Prammanee, Siripatr; Lersrutaiyotin, Rewat (Journal of Food Health and Bioenvironmental Science, 2018)
There have been several reports suggesting that the tissue culture technique produced genetic variations of somaclones from a wild type plant. In this study, SSR markers was used to detect the genetic variation in regenerated plants from leaves and shoots via callus culture of sugarcane variety K84-200. DNA from 58 somaclones and the wild type plant K84-200 were isolated. Ten primers of simple sequence repeat (SSR) markers were used to determine mutation of somaclones. Among all ten ampliﬁed SSRs, 3 primers MCSA205C07, SMC226CG and SMC319CG showed different polymorphisms from the wild type plant. The clustering analysis separated 58 somaclones and the wild type plant into 2 groups. The wild type is in group A while group B was different from the wild type in regards to DNA pattern and sequence variations including insertions, deletions, and substitutions in somaclones. This result showed that the somaclonal variation technique can induce genetic variation from the wild type. SSR markers and sequencing of SSR polymorphic bands are a useful tool for detection of genetic variations in somaclones.